Integrated Strategies for Teaching Arabic Skills at Raudlatul Hidayah Islamic Boarding School - Qulyubi Rais; Muassomah; R. Taufiqur Rochman; Rachmad Ramadhan (Lisanudhad: Jurnal Bahasa, Pembelajaran dan Sastra Arab, 2026)
This study examines the integrated strategies used to teach Arabic language skills at Raudlatul Hidayah Islamic Boarding School, Sulusuban, Central Lampung. The study focuses on four core skills: listening, speaking, reading, and writing. It aims to describe how these skills are developed through pesantren-based learning practices and to identify the challenges encountered in their implementation. This research employs a qualitative case study design, with data collected through observation, interviews, and documentation of Arabic learning activities. The findings show that listening skills are developed through murattal Qur’anic recitation, Arabic lectures, and dialogue recordings; speaking skills are strengthened through muhadharah, thematic conversations, and daily Arabic interaction; reading skills are taught through talaqqī, bandongan, classical texts, and selected modern materials; while writing skills are practiced through journals, summaries, and short compositions. These strategies indicate an effort to integrate traditional pesantren methods with communicative Arabic teaching. However, their implementation is still limited by inadequate learning media, uneven student proficiency, limited teacher training, and the absence of structured skill-based assessment.